PENGEMBANGAN E-BOOK MENGGUNAKAN APLIKASI ANIMAKER PADA MATERI BANGUN DATAR - Adhisti Rizki Ayuni Sudanarto; Elly Sukmanasa; Santa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mathematics is one of the subjects that is synonymous with mathematical abilities, one of which is the ability to understand concepts, with the ability to understand concepts makes it easier for students to solve problems because students will be able to relate and solve these problems with concepts they have understood. This study aims to obtain results and describe the development of animated videos using animaker to improve the ability to understand concepts in learning on flat shapes. This type of research is a development research with an RnD approach. The main objective of this study is to produce a learning media product in the form of a research and development (R&D) type of learning media. This research was developed using the five steps of the ADDIE development model, namely 1) analyze, 2) design, 3) development, 4) implementation, 5) evaluation. Data collection techniques used were interviews, observations, and questionnaires. This study produced learning media using the Animaker Application based on the validation that has been carried out which resulted in a "very good" category. The validation results show that the learning media product is worthy of being tested on students. The results of the field trial resulted in a "good" category. Thus, the mathematics learning media product created by the researcher is worthy of being used in the learning process.